Anterior Cruciate Ligament Injuries Change Muscle Co-Activation Strategies in Adolescent Females During Landing. Issue 5 (31st May 2022) - Bel, Michael Del; Romanchuk, Nicholas J.; Benoit, Daniel; Carsen, Sasha
Background: Anterior cruciate ligament (ACL) injuries in adolescents continue to rise. Given that muscles are the only modifiable contributors to knee joint control, there has been a focus on their management in rehabilitation research. After an ACL injury, increased co-activation of the thigh muscles is considered a hallmark characteristic in stabilising the knee joint among adults with ACL injuries. However, increasing co-activation to improve joint stiffness should not be the rehabilitation goal after an ACL injury since a prolonged increase in co-activation about the joint alters knee joint loads and is associated with the onset and progression of knee osteoarthritis in adults. Purpose: Co-activation information currently does not exist among adolescents, therefore this study set out to address this gap. Methods: Twelve female patients with ACL-deficiency (ACLd) and 12 matched controls (CON) performed countermovement jumps while having the following muscle activations recorded for both limbs: rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), biceps femoris (BF), semitendinosus (ST), lateral (LG) and medial gastrocnemii (MG), and gluteus medius (GM). During the landing phase of the task, co-activation indices were calculated for the lateral thigh muscles (VL and ST), medial thigh muscles (VM and BF), and the total thigh muscles (VL&VM and BF&ST). Independent-sample t-tests ( p =.05) evaluated mean group differences for each of the three co-activation indices. Results: A significant difference was found in medial co-activation ( p =.019), while a trend towards significance ( p =.071) was found in total thigh co-activation, with ACLd females having higher co-activations indices in both compared to matched controls (Figure 1). No differences were observed between groups in their demographics or lateral co-activation indices. Conclusion: Failure to appropriately adapt one's neuromuscular control strategies may explain why some individuals continue to have knee instability and difficulty returning to their pre-ACL injury activity levels after rehabilitation. This is evidenced by our findings among this cohort of females with ACL injuries who displayed higher co-activations, specifically in the medial thigh musculature. Moreover, our findings highlight the need to target individual muscles during rehabilitation and to avoid generalization of segment muscles (i.e. quadriceps and hamstrings) where vital information in knee joint stabilization may be missed. Figure 1. Group means of lateral (vastus lateralis and semitendinosus), medial (vastus medialis and biceps femoris), and thigh co-activation (quadriceps and hamstrings) indices for ACLd and CON participants during countermovement jumps; * signifies a significant difference between groups.